Study of surface roughness on induction hardened steel using CBN cutting tool - S. , Thamizhmanii
The hard turning is stand for substitute for grinding process and avoids coolant. Many researches had conducted study and found that it is possible to super finish hard material and possible to obtain surface roughness of 2 – 8 μm by using advanced cutting tool materials like ceramic, CBN and PCBN. The coated ceramic tool was used to machine SCM 440 induction hardened material. The hardness of the material was between 60 to 65 HRC. The turning process was carried under dry cutting condition. There were improvements in surface roughness at high cutting speed, low feed and low depth of cut. There were variations in surface roughness at the point where the hardness is high. Nose wear were dominant in the tool during turning than any other wear.